CSR communication & stigmatized industries: is inclusion and diversity becoming a means for stigma-washing? Six decades of literature review - Alonso, Juan Manuel; Illia, Laura; Rodríguez-Cánovas, Belén (Cuadernos.info, 2024)
This work aims to present an in depth literature review under the lens of three disciplines: Corporate Social Responsibility (from now on CSR) communications, stigmatized industries, and diversity and inclusion (D&I). Such review is supported by a bibliometric mapping software, SciMAT, developed by Cobo and colleagues (2011), at Universidad de Granada, Spain. A total of 8,942 papers on the three topics from 1963 to 2022 published in 98 leading journals indexed in the Journal Citation Reports of the Web of Science have been examined. The aforementioned software has been used to identify the relevant studies to focus on a second in-depth qualitative individual scrutiny. Findings suggest that the use of D&I to mitigate organizational stigma has yet to be analyzed. One still needs to confirm or reject the proposition that stigmatized firms use CSR communication and D&I to mitigate their stigma. Furthermore, they indicate that if future studies may find that stigmatized companies utilize D&I to manage their stigma via CSR communication, the D&I discipline would suffer from this practice, since one would prove that D&I is instrumentally used in a different way than it is supposed to.